PENGARUH MODEL PEMBELAJARAN CASE BASED LEARNING TERHADAP HASIL BELAJAR KOGNITIF SISWA PADA MATA PELAJARAN IPAS DI SEKOLAH DASAR - Fatimah Azzahra Nugroho; Anas Salahudin; Ani Yanti Ginanjar (Jurnal Pendidikan Dasar, 2026)
Science learning in elementary schools still shows low cognitive learning outcomes, marked by an average student score of 55 which is below the KKM of 65. This condition is influenced by learning that is still teacher-centered so that students are less involved in problem solving. The Case Based Learning (CBL) model is considered capable of improving learning outcomes because it presents real cases that encourage students' activeness and critical thinking. This study aims to determine the level of CBL implementation, students' cognitive learning outcomes, and the relationship and influence of CBL on the cognitive learning outcomes of fifth-grade students. The study used a quantitative approach with a correlational method. The research sample consisted of 30 fifth-grade students. The research instruments were a CBL implementation questionnaire and a science learning outcome test. The results showed that the implementation of CBL was in the very high category, students' cognitive learning outcomes were also in the very high category, and there was a strong relationship between the implementation of CBL and cognitive learning outcomes with a correlation value of 0.697 and a significance of <0.05. The CBL model contributed 48.6% to students' cognitive learning outcomes. Thus, Case Based Learning has been proven to have a positive effect in improving students' cognitive learning outcomes in science